Exploring factors influencing physiotherapists' perceptions of measuring reactive balance following a theory-based multi-component intervention: a qualitative descriptive study. Issue 17 (14th August 2022) - Sibley, K. M.; Gardner, P.; Bentley, D. C.; Khan, M.; McGlynn, M.; Shing, P.; Shaffer, J.; O'Hoski, S.; Salbach, N. M.
Abstract: Purpose: Reactive balance is a critical consideration for mobility and fall avoidance, but is under-assessed among physiotherapists. The objective of this study was to explore factors influencing physiotherapist perceptions about measuring reactive balance upon completion of a 12-month theory-based, multi-component intervention to increase use of a measure of reactive balance. Methods: A qualitative descriptive approach was used. Semi-structured interviews were conducted with 28 physiotherapists treating adults with balance impairment in three urban Canadian rehabilitation hospitals that participated in the intervention. Interviews explored perceptions of reactive balance measurement and perceived changes in clinical behavior. Thematic analysis involved multiple rounds of coding, review and discussion, theme generation, and interpretation of findings through individual analysis and team meetings. Findings: Participants expressed contrasting views about integrating reactive balance measurement in their practice, despite consistent acknowledgement of the importance of reactive balance for function. Three themes were identified highlighting factors that mediated perceptions about measuring reactive balance: patient characteristics; trust between physiotherapist and patient; and the role of physiotherapist fear. Conclusions: The findings highlight that decision making for measuring reactive balance in rehabilitation settings is complex. There is a need for additional work to facilitate long-term implementation of clinical reactive balance measurement, such as refining patient criteria for administration, ensuring sufficient time to establish a trusting relationship, and developing and testing strategies to address physiotherapist fear. IMPLICATIONS FOR REHABILITATION: Reactive balance is important for falls prevention and mobility, but is under-assessed among physiotherapists. This study identified three factors that influenced uptake of reactive balance measurement among physiotherapists in rehabilitation settings: patient characteristics; trust between physiotherapist and patient; and the role of physiotherapist fear. Knowledge of the identified factors may assist with design and use of reactive and other balance measurements. Strategies aimed at developing trusting relationships between physiotherapist and patient along with addressing physiotherapist fear could facilitate the uptake of clinical reactive balance measurement.